Spectroscopic Ellipsometry Characterization of As-Deposited and Annealed Non-Stoichiometric Indium Zinc Tin Oxide Thin Film - Janicek, Petr; Putri, Maryane; Kim, Ki Hwan; Lee, Hye Ji; Bouska, Marek; Šlang, Stanislav; Lee, Hee Young (MDPI AG (Multidisciplinary Digital Publishing Institute), 2021)
A spectroscopic ellipsometry study on as-deposited and annealed non-stoichiometric indium zinc tin oxide thin films of four different compositions prepared by RF magnetron sputtering was conducted. Multi-sample analysis with two sets of samples sputtered onto glass slides and silicon wafers, together with the analysis of the samples onto each substrate separately, was utilized for as-deposited samples. Annealed samples onto the glass slides were also analyzed. Spectroscopic ellipsometry in a wide spectral range (0.2–6 eV) was used to determine optical constants (refractive index n and extinction coefficient k) of these films. Parameterized semiconductor oscillator function, together with Drude oscillator, was used as a model dielectric function. Geometrical parameters (layer thickness and surface roughness) and physical parameters (direct optical bandgap, free carrier concentration, mobility, and specific electrical resistivity) were determined from spectroscopic ellipsometry data modeling. Specific electrical resistivity determined from the Drude oscillator corresponds well with the results from electrical measurements. Change in the optical bandgap, visible especially for annealed samples, corresponds with the change of free carrier concentration (Moss– Burstein effect). Scanning electron microscope did not reveal any noticeable annealing-induced change in surface morphology.
Keywords: optical properties; spectroscopic ellipsometry; RF magnetron sputtering; indium zinc tin oxide; non-stoichiometric